2011
DOI: 10.1038/onc.2011.238
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin1 mediates metastatic growth of breast cancer cells by facilitating HIF-1-dependent VEGF expression

Abstract: β-arrestins 1 and 2 are multifunctional adaptor proteins originally discovered for their role in desensitizing seven-transmembrane receptor signaling via the heterotrimeric guanine nucleotide binding proteins. Recently identified roles of β-arrestins include regulation of cancer cell chemotaxis and proliferation. Herein we report that β-arrestin1 expression regulates breast tumor colonization in nude mice and cancer cell viability during hypoxia. β-arrestin1 robustly interacts with nuclear hypoxia-induced fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 47 publications
3
62
0
Order By: Relevance
“…The ARRB1 also induce hypoxia and may help in cancer cells growth and metastasis 44,45 . The IHC results clearly indicate that the ARRB1 expression gets downregulated with the advancing cancer stage.…”
Section: Discussionmentioning
confidence: 99%
“…The ARRB1 also induce hypoxia and may help in cancer cells growth and metastasis 44,45 . The IHC results clearly indicate that the ARRB1 expression gets downregulated with the advancing cancer stage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there have been mounting researches focusing on the effects and mechanisms of β-arrestin1 on the tumorigenesis and progression of several malignant tumors [10][11][12][13]34]. It is worthy of note, however, that the reports on β-arrestin1 expression in lung adenocarcinoma are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…These give investigators a new inspiration that β-arrestin1 plays a vital role in transcriptional regulation in cell growth, apoptosis, and modulation of immune functions [7][8][9]. Meanwhile, there are increasing evidences that nuclear β-arrestin1 contributes to tumor growth, invasion, and metastasis in multiple malignancies such as breast cancer, colorectal cancer, lung cancer, and prostate cancer [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Although proteomic analysis has revealed that b-arr1 may directly interact with many proteins, 13 no data have been previously reported regarding the interaction of b-arr1 with b-catenin. Apart from the role of b-arr1 into regulating b-catenin signaling in the cytosolic compartment, 5,25-27 our findings unveil a novel role of b-arr1 as a nuclear platform in b-catenin transcriptional activity, depending on its subcellular nuclear distribution thus accounting for the epigenetic modification and gene transcription of selected target genes.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, b-arr1 regulates nuclear signaling during hypoxia to promote survival of breast cancer cells by facilitating hypoxia-inducible factor-1-dependent vascular endothelial growth factor expression. 20 Recent results show that b-arr1, via the interaction with importin b1, is imported in the nucleus where it is able to recruit protein modifiers to p65/RelA, consequently increasing nuclear factor-kB transcriptional responsiveness. 21 However, the underlying mechanisms of b-arr1-mediated transcription regulation in pathophysiological conditions, such as cancer, still remain to be elucidated.…”
Section: Epithelial Ovarian Cancer (Eoc) Often Features Endothelin (Ementioning
confidence: 99%